Modified Power Piston Versus Simultaneous Stapedotomy With Hearing Aids in Otosclerosis: A Follow-Up Study Exploring Speech Recognition, Quality of Life and Usage of Device. Issue 4 (16th April 2022) - Dejaco, Daniel; Riedl, David; Cassar, Anna Elisabeth; Gottfried, Timo; Rasse, Thomas; Fischer, Natalie; Kreuzer-Simonyan, Armina; Seebacher, Josef; Riechelmann, Herbert; Keintzel, Thomas; Schmutzhard, Joachim
Abstract : Objective: To compare audiologic outcomes, quality-of-life (QoL) and usage-of-device (UoD) between case-matched, otosclerotic patients with mixed hearing loss (MHL) which received (a) stapedotomy and postoperative amplification with hearing aids (SDT+HA) or (b) short-incudial process coupled active middle ear implant with simultaneous stapedotomy (mPP). Study design, setting, and patients: Prospective, matched case-control, follow-up study conducted at two tertiary otologic referral centers. Eligible were all otosclerotic patients with MHL, which received mPP at either of the two institutions. A case-matched-cohort of SDT+HA-patients was generated from the hospitals database based on preoperative audiologic findings. Main outcome measures: For sound- and speech perception, primary outcome parameters were the mean postoperative, aided air-conduction pure tone average (mpa-AC-PTA) and word recognition score at 80 dB speech level (mpa-WRS), for QoL the mean Nijmegen-Cochlear-Implant-Questionnaire (NCIQ) total-score, and for UoD the mean score rated on a 10-point Likert-scale. Results: A total of 28 patients were included; 14 received mPP; mpa-AC-PTA and mpa-WRS significantly improved from 47.1 dB-HL to 34.3 dB-HL (−12.8 dB-HL; p  < 0.001) and from 75.0% to 93.2% (+18.2%; p  = 0.002) compared to 46.5 dB-HL to 31.9 dB-HL (−14.8 dB-HL; p  < 0.008) and 75.0% to 93.2% (+18.2%; p  = 0.002) for SDT+HA. No significant difference between groups was observed (all p  > 0.1). NCIQ total-score between groups did not significantly differ (70.4 vs. 69.9; p  = 0.93). UoD for mPP was significantly higher (6.1 vs. 3.0; p  < 0.001). Conclusions: If medical/technical problems prevent usage of HA in otosclerosis with MHL, mPP can be considered as effective treatment option with similar audiological outcome and QoL. A significantly higher UoD for mPP was observed.